Effects of Repetitive Transcranial Magnetic Stimulation on the Somatosensory Cortex during Prism Adaptation. Issue 2 (April 2014) - Yoon, Hee-Chul; Lee, Kyung-Hyun; Huh, Dong-Chan; Lee, Ji-Hang; Lee, Dong-Hyun
Although the behavioral characteristics and the neural correlates of prism adaptation processes have been studied extensively, the underlying mechanism is yet to be investigated. Recently, somatosensory suppression was heralded as a mechanism for the sensory re-alignment process accompanying the adaptation. Somatosensory suppression should facilitate the re-alignment process in the proprioceptive system. The shift in the proprioceptive system takes place mostly during a concurrent visual feedback (CVF) condition; during a terminal visual feedback (TVF) condition, the visual system experiences significant adaptation (visual shift), so somatosensory suppression should have minimal functional consequences under TVF. To test this hypothesis, a repetitive transcranial magnetic stimulation (rTMS) was applied to the primary somatosensory cortex as an artificial somatosensory suppression right after the reaching initiation in CVF and TVF conditions, and changes in adaptation were observed. Because somatosensory suppression is already in effect during CVF, rTMS would cause no significant changes. During TVF with rTMS, however, significantly different patterns of adaptation could be expected when compared to a sham rTMS condition. Young adults ( N = 12) participated in 4 sessions (CVF/TVF, real/sham rTMS); visual, proprioceptive, and total shifts were measured. Movement time and curvature of the reaching movement were measured during the adaptation phase. Results showed that while the total shift was unchanged, the proprioceptive shift increased and the visual shift decreased in the TVF condition when rTMS was delivered. However, the total, proprioceptive, and visual shifts were not influenced by rTMS in the CVF condition. Suppression of proprioception induced by the rTMS could be one of the requisites for successful proprioceptive shift during prism adaptation.